Does Fiscal Decentralization Increases Regional Income Inequality in Indonesia? - Afief El Ashfahany; Rifi Fazrina Djuuna; Nur Fahmi Rofiq (Jambura Equilibrium Journal, 2020)
This paper examines the impact of fiscal decentralization on regional income inequality in Indonesia. This study employs dynamic panel data analysis–the two-step system generalized method of moments (GMM) on 2008-2017 regional level datasets. This study found that regional income inequality indeed increases during the implementation of fiscal decentralization and appears to be exceptionally high for rich provinces. Essentially, this study suggest that fiscal decentralization appears to increase regional income inequality in Indonesia. The results might be due to low regional fiscal capacity in Indonesia, which induces high dependency of local government that further restraints local competition in public goods provision. Keywords: fiscal decentralization, regional income inequality, generalized method of moments (GMM).